Obesity, Pregnancy Complications, and Birth Outcomes - Marshall, Nicole E.; Spong, Catherine Y. (Seminars in Reproductive Medicine, 2012)
Obesity is an increasingly common complication of pregnancy with over half of all women in the United States starting pregnancy overweight or obese. Obese women face unique physiological changes during pregnancy, and these women and their neonates are at increased risk for perinatal morbidity and mortality. In this review, we discuss physiological alterations in obese pregnant women and examine obesity-related antepartum, intrapartum, and postpartum complications along with management options.
Keywords: obesity; pregnancy; complications; perinatal; morbidity; mortality